Training of the Aesthetic Being Connecting Sri Aurobindo's Ideas of the Visual in Education Across Cultures - KRISTI OLIVER; MAUREEN P. HALL (Dr. Chinmay Pandya, 2017)
This paper grows out of the collaboration between an English Educator and an Art Educator who both work with pre service and in-service teachers as they prepare for teacher licensure. Through ongoing conversations about shared interests, the collaboration now has connected the East and West. More specifically, this paper connects Sri Aurobindo's ideas about education and self-education, ones that privilege the visual and aesthetic, to theories and practices in US Education. Aesthetic Education is at the center of this work. We believe that engaging with artwork, artifacts, and visual culture, provides learners with opportunities to explore the unfamiliar as a way to understand the familiar, enhancing a greater worldview. Ideas from theorists in the West, such as John Dewey and Maxine Greene, along with strategies for visual analysis based on Feldman and Yenawine, align with and are enhanced by Sri Aurobindo's ideas about education. Through the about power of Intercultural Education, the interconnections and connections begin to knit together East and West, opening a broader worldview in the service of improving education.